2019
DOI: 10.3329/bjms.v19i1.43886
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Complications of Newborns with Birth Defect: A Hospital based Case-Control Study

Abstract: Background: Birth defect is one of the most important causes of neonatal mortality worldwide. In a developing country like Bangladesh many possible factors for birth defects are present which should be identified. This study was performed to determine those risk factors of birth defect and complications associated with it. Materials and Methods: A hospital based matched case-control study was conducted from August 2015 to July 2016 in department of Neonatology along with Obstetrics and Gynecology at BSMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…Birth defects were more common in male (male 59%, female-38%, M:F-2:1) in this study .Similar male preponderance were observed in Amin T et al 11 , Banu et al 14 , Fatema et al 16 and Afroze s et al 17 studies from Bangladesh and Hossain et al and Sanker et al studies from India 13,15 . It may be because of the fact that the females were afflicted with more lethal congenital malformations and could not survive to be born with signs of life.…”
Section: Resultsupporting
confidence: 84%
See 1 more Smart Citation
“…Birth defects were more common in male (male 59%, female-38%, M:F-2:1) in this study .Similar male preponderance were observed in Amin T et al 11 , Banu et al 14 , Fatema et al 16 and Afroze s et al 17 studies from Bangladesh and Hossain et al and Sanker et al studies from India 13,15 . It may be because of the fact that the females were afflicted with more lethal congenital malformations and could not survive to be born with signs of life.…”
Section: Resultsupporting
confidence: 84%
“…13 16 . Other studies done by Amin T et al and Afroze s et al found that cardiovascular system defect was most common defect followed by musculoskelstal system defect 11,17 .…”
Section: Resultmentioning
confidence: 86%
“…Outros estudos também apontaram o menor número de consultas pré-natais como fator associado ao nascimento com malformações congênitas. (30,33) A organização de boas consultas pré-natal, o fortalecimento da atenção primária à saúde e a suplementação com ácido fólico são medidas profiláticas simples, porém eficazes, de prevenção para malformações congênitas. (34) O início do acompanhamento pré-natal ainda nas primeiras semanas de gestação e a realização do número de consultas preconizadas permite detectar precocemente alterações no feto, bem como previne a exposição a fatores ambientais e teratogênicos.…”
Section: Discussionunclassified
“…It is reported that among risk factors for foetal anomaly is diabetes mellitus. 4 By saying that, the patient is free of any risk factors which might not explain why she got conjoint twin pregnancy. Twins pregnancy, in general, might give a different joy to the parent but having conjoined twins may cause another complete surprise.…”
Section: Discussionmentioning
confidence: 99%